A most painful knee does not induce interlimb differences in knee and hip moments during gait in patients with knee osteoarthritis - Bakker, Nienke F.; Schrijvers, Jim C.; van den Noort, Josien C.; Hall, Michelle; van der Krogt, Marjolein M.; Harlaar, Jaap; van der Esch, Martin (Clinical biomechanics (Bristol), 2021)
Patients with knee osteoarthritis can adapt their gait to unload the most painful knee joint in order to try to reduce pain and improve physical function. However, these gait adaptations can cause higher loads on the contralateral joints. The aim of the study was to investigate the interlimb differences in knee and hip frontal plane moments during gait in patients with knee osteoarthritis and in healthy controls. Forty patients with knee osteoarthritis and 19 healthy matched controls were measured during comfortable treadmill walking. Frontal plane joint moments were obtained of both hip and knee joints. Differences in interlimb moments within each group were assessed using statistical parametric mapping and discrete gait parameters. No interlimb differences were observed in patients with knee osteoarthritis and control subjects at group level. Furthermore, the patients presented similar interlimb variability as the controls. In a small subgroup (n = 12) of patients, the moments in the most painful knee were lower than in the contralateral knee, while the other patients (n = 28) showed higher moments in the most painful knee compared to the contralateral knee. However, no interlimb differences in the hip moments were observed within the subgroups. Patients with knee osteoarthritis do not have interlimb differences in knee and hip joint moments. Patients and healthy subjects demonstrate a similar interlimb variability in the moments of the lower extremities. In this context, differences in knee pain in patients with knee osteoarthritis did not induce any interlimb differences in the frontal plane knee and hip moments. •No significant interlimb differences in frontal plane knee and hip moments were found.•Patients show a similar interlimb variability as healthy controls.•A subgroup of patients had a lower moment in the most painful knee joint.•This subgroup showed no interlimb differences in the hip moments.